The Influence of Intercultural Communication by the Banua Niha Keriso Youth Commission on the Preservation of Nias Cultural Values in Tangerang City - Telaumbanua, Timothy Euodia; Lubis, Lusiana Andriani; Zulkarnain, Iskandar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the impact of intercultural communication by the Banua Niha Keriso Youth Commission (KNBK) on preserving the cultural values of the Nias tribe in Tangerang City. The research was conducted through a series of cultural activities, educational workshops, and dialogue sessions over six months, involving 150 participants from the Nias community. The findings reveal a significant positive influence of intercultural communication on the preservation of Nias cultural values, especially among the younger generation. The implications highlight the necessity of continuous cultural education and active community engagement to sustain cultural heritage in urban settings